The Effect of Healthy Boba Pearl Drink on Post-Prandial Glucose - Jaelani, Mohammad; Larasati, Meirina Dwi; Muninggar, Dian Luthfita Prasetya; Wulandari, Desi; Rosidi, Ali (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study was a randomized controlled trial using a repeated experimental design with a pre-test and a post-test control group. The study subjects were women of childbearing age, aged 20‒30 years, with no diagnosed chronic diseases and with baseline fasting blood glucose levels less than 125 mg/dL. Participants were randomly assigned to treatment and control groups. The treatment group received 350 mL of healthy boba drink, while the control group received 350 mL of commercial boba drink. The healthy boba drink was made by mixing 67 mL of fresh milk, 133 mL of soy milk, 1 g of stevia sweetener, 100 g of red dragon fruit, and 40 g of healthy boba pearls. It contained 215 kcal of energy, 8.82 g of protein, 8.90 g of fat, 30.78 g of carbohydrate, and 1,808 g of fiber. Each group had an initial fasting blood glucose levels measurement before the intervention, and postprandial glucose levels were measured at the end of the intervention (one time of intervention). The collected data were analyzed univariately to analyze the effect of treatment on postprandial glucose using the independent t-test. The result indicated that the subjects in the treatment group and 96.2% of the subjects in the control group had fasting glucose levels less than 126 mg/dL. Both participants in the control and treatment groups had postprandial glucose levels less than 200 mg/dL. The mean glucose level was 89.49 mg/dL in the treatment group and 92.57 mg/dL in the control group. The study results showed that the treatment group that consumed the healthy boba drink had a lower average postprandial glucose level than the control group. The statistical test results showed that there was a significant effect of healthy boba drink consumption on postprandial glucose levels in the treatment group (p<0.000). It is concluded that the healthy boba drink intervention had a significant effect (p<0.000) on lowering blood glucose by 5.82 mg/dL after the initial treatment. The results of this study are a major first step for future work to develop a healthier boba drink.